Ed Bacon : planning, politics, and the building of modern Philadelphia - Heller, Gregory L. (City in the twenty-first century book series., 2013)
Ed Bacon is the first biography of the innovative and controversial urban planner who transformed Philadelphia in the mid-twentieth century.